Integrating Digital Learning to Enhance Learning Motivation in Early Childhood Education: Evidence from Raudlatul Athfal - Lathi Fatul Alfiani; Khotimatus Sholikhah; Winnuly Winnuly (AFKARINA: Jurnal Pendidikan Agama Islam, 2026)
This study aims to describe the integration of digital learning in improving early childhood learning motivation at RA Darul Ilmi Widang Tuban. The need for concrete, fun, interactive, and appropriate early childhood learning is very important, considering the characteristics of child development. This study uses a descriptive qualitative approach supported by simple quantitative data. The research subjects included the principal of an Islamic kindergarten, Group B teachers, and Group B students aged 5–6 years. Data collection techniques were carried out through interviews, observation, and documentation. Data were analyzed through data reduction, data presentation, drawing conclusions, and calculating the average score of children's learning motivation observations. The results showed that the integration of digital learning was carried out through the use of laptops, learning videos, educational applications, and interactive songs planned in the daily lesson plan, used two to three times a week, and placed in the opening, core activities, and closing stages. Digital media was not used as a substitute for play learning, but as a pedagogical stimulus combined with discussion, drawing, playing, and direct practice. This integration had a positive impact on children's learning motivation, which was evident in interest, attention, activeness, enthusiasm, pleasure, and perseverance.